Інноваційність у захисті методом використання сучасних інструментів для контроля за кібербезпекою - Малахова, А. А. (ХНУРЕ, 2024)
In the rapidly evolving landscape of cybersecurity threats, the importance of innovative approaches to protection cannot be overstated. This whitepaper explores the importance of using modern tools and techniques in cybersecurity control to effectively mitigate risks. By leveraging advanced technologies such as behavioural analytics and threat intelligence platforms, organizations can strengthen their defences against a wide range of cyber threats. This explores the various applications of these tools, from proactive threat detection to rapid incident response and remediation. By embracing innovation and leveraging modern tools for cybersecurity control, organizations can enhance their resilience against cyber attacks and safeguard their sensitive data in a digital environment.
Keywords: кібербезпека